Metaphorical Analysis and the Meaning of the Song “Another One Bite the Dust” by Queen - Adristi Yajna Zulaika; Chairinnisa Artanti; Cut Putri Alivia; Dira Annisa; Dian Marisha Putri (JURNAL EDUKASI NONFORMAL, 2023)
A metaphor is a figure of speech that contrasts two unrelated items and helps in the communication of complex ideas or emotions by drawing on familiar or concrete concepts. Metaphor is often utilized in poetry, novels, films, songs, and so on. This study provides a metaphorical analysis of the lyrics to "Another One Bites The Dust," a hit song by the British rock band Queen published in 1980. Using a semantic approach, the study investigates the numerous layers of meaning provided by the song's lyrics, which have been interpreted variously by fans and critics throughout the years. The paper offers a detailed analysis of the song's metaphors and the function of the metaphors, including analyzing the metaphor "another one bites the dust" as a euphemism for death in one Santa Fe High School shooting in 2018, one of the deadliest mass shootings in the United States. The study concludes by reflecting on the song's lasting popularity and cultural relevance, as well as the difficulties and opportunities associated with understanding metaphorical meaning in popular music. Based on the analysis, the writers discovered 15 metaphor data and 4 metaphor functions in the lyrics of "Another One Bites.